The Interplay of Environmental, Socio-Cultural, and Community-Based Interventions in Reducing Cardiovascular Disease Risk in Indonesia: A Systematic Review - Akmal Gani Ariansyah; MG. Catur Yuantari; Adian Khoironi (BIORE Scientia Publisher, 2025)
Cardiovascular disease (CVD) represents a profound global health challenge, contributing to an estimated 17.9 million deaths annually worldwide. In Indonesia, the burden of CVD is particularly significant, with coronary heart disease prevalence at 1.5% and Non-Communicable Diseases (NCDs), including CVD, accounting for 73% of all fatalities. Community-based programs, such as Prolanis, have been implemented as key intervention strategies. This systematic review analyzes the effectiveness of these programs in reducing CVD risk factors among NCD patients in Indonesia, examining their impact within the complex environmental and socio-cultural context. The methodology involved collecting articles from Google Scholar, PubMed, and ScienceDirect, applying keywords in PICO format, and filtering using the PRISMA flow diagram, ultimately including six articles for detailed analysis. Findings indicate that community-based programs generally contribute positively to controlling cardiovascular risk factors through health education and regular monitoring. However, effectiveness varies, influenced by intervention duration, participant adherence, and individual health conditions. This variability underscores the profound influence of broader environmental factors, including air and water quality, food environment, green space access, waste management, and noise pollution, all prevalent challenges in Indonesia. Furthermore, socio-cultural factors, such as traditional health beliefs, communal habits like gotong royong, and socioeconomic disparities, significantly mediate program acceptance and adherence. This analysis highlights the imperative for holistic, context-specific, and interdisciplinary approaches to CVD prevention in Indonesia, integrating public health interventions with environmental improvements and culturally sensitive strategies to enhance overall program effectiveness and sustainability.